Cutaneous and Systemic Psoriasis: Classifications and Classification for the Distinction - Yan, Bing-Xi; Chen, Xue-Yan; Ye, Li-Ran; Chen, Jia-Qi; Zheng, Min; Man, Xiao-Yong (Frontiers in Medicine, 2021)
Psoriasis is a chronic multisystem inflammatory disease that affects ~0.1–1.5% of the world population. The classic cutaneous manifestation of psoriasis is scaly erythematous plaques, limited or widely distributed. Moreover, psoriasis could be associated with comorbidities like psoriatic arthritis, metabolic syndrome, diabetes, cardiovascular disease, nephropathy, bowel disease, and brain diseases. In this review, we suggest that psoriasis should be classified as cutaneous psoriasis or systemic psoriasis and propose the classification for distinction. This would help to better understand and manage psoriasis.